EFFECT OF PROCESSED CHICKEN FEET CONSUMPTION IN INCREASING BLOOD CALCIUM LEVELS AMONG FEMALE ADOLESCENTS - MULYANI, NUNUNG; ROHMATIN, ETIN; PRAPAHLAWANTI, IR IR KHAIRIYAH; MARDIANI, DITA EKA; GANTINI, DEDE; HERLIANI, YULIA; SUPTIANI, LAILA PUTRI; SAHLAN, MUHAMAD; IRIANTI, BAYU (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to examine the effect of processed chicken feet consumption for a month in increasing blood calcium levels among female adolescents. Methods: This study was carried out using a quasi-experimental method by measuring blood calcium levels before and after the daily consumption of 100 grams of processed chicken feet for a month. Furthermore, the sample population comprised 105 female adolescents who met the inclusion and exclusion criteria. Blood calcium measurement was performed using the OCP direct colorimetric lab test, data processing used the Intention to Treat (ITT) method, and data analysis was carried out using the Wilcoxon test (α=5%). Results: A significant difference was observed between blood calcium levels before and after the consumption of processed chicken feet over 1 mo, with an average increase of 1.10 mg/Dl. Conclusion: Based on the results, blood calcium levels experienced an increase of 1.01 mg/Dl, equivalent to the consumption of a 500 mg/day calcium tablet.